Amalgamation Practices Among Moro Tribes in Bangsamoro Region - Princess Sheryn A Mamucao; Noraida S. Balading; Analiza B. Angin; Aslanie G. Balao; Richelle L. Angi (RIRAI Publisher, 2026)
This study examines the practices and challenges of intermarriage among Moro tribes in Poblacion Balabagan, Lanao del Sur, and Bayanga Norte, Matanog, Maguindanao del Sur, where intermarriage is prevalent. The research explores the motivations for intermarriage, how couples navigate cultural differences, and the practices involved in their marriages. Using a phenomenological approach, data were collected through interviews with intermarried individuals knowledgeable about intermarriage practices. Findings indicate that while intermarriage is common, the specific customs and rituals vary by tribe, with all couples ensuring adherence to Islamic traditions. Notable differences include traditional wedding ceremonies, such as the performance of the kulintang at Maguindanaon weddings. The study highlights the role of social workers in supporting intermarried couples, particularly through counseling, as they navigate cultural and familial challenges. This research provides valuable insights for social work professionals addressing family dynamics in the context of growing intermarriage rates.